PERLINDUNGAN HUKUM BAGI KONSUMEN TERKAIT KETENTUAN PERUBAHAN SEWAKTU-WAKTU TERHADAP BESARAN TAGIHAN BULANAN DALAM KONTRAK BERLANGGANAN PAKET INDIHOME - Nikmah, Nur Laili; Nugroho, Arinto (NOVUM : JURNAL HUKUM, 2019)
Abstract PT Telkom is a company owned by a State-Owned Enterprise (BUMN) which is engaged in the IndiHome service provider which has a subscription contract. The agreement between PT Telkom and consumers has a standard clause regarding changes at any time. As explained in Pasal 18 section (1) of the UUPK, an agreement should not include an exsoneration clause. This writing aims to understand whether the provisions for changing the amount of monthly bills in the IndiHome package subscription contract is a violation of the UUPK and understanding how the form of legal protection for consumers against the clause of the occasional change in the monthly bill amount in the IndiHome package subscription contract. Method used normative juridical research, using a statutory approach and a conceptual approach. The results of the research and discussion show that the provision regarding changes at any time to the amount of monthly bills in the subscription contract are contrary to the rules for the inclusion of standard clauses contained in Pasal 18 section (1) letter g of the UUPK. The agreement that the consumer has agreed with IndiHome has no legal force so that the agreement is null and void based on Pasal 1320 KUHPer. Principle of agreement law, that IndiHome and consumers have the freedom to make agreements, but still pay attention to consumer rights as stipulated in Pasal 4 of the UUPK. Legal protection provided to consumers is preventive legal protection and repressive legal protection. Keywords: Legal Protection, Consumers, Subscription Contracts, IndiHome